Predictors of Secondary Postpartum Hemorrhage: A Hospital-Based Cross-Sectional Study - Mabruka Faizah; Nasreen Akther; Shahana Ferdous Choudhury; Lubna Yeasmin; Fatama Tul Tanzina Chowdhury; Mohammad Nurunnabi (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2026)
Background: Hemorrhage has been a leading cause of maternal deaths in Bangla desh over the past decade. Postpartum Haemorrhage (PPH) is one of the leading causes of maternal death worldwide. It is a life-threatening condition and a serious obstetric emergency. The aim of the study is to explore the predictors of secondary postpartum haemorrhage in a medical college hospital. Materials and methods: A hospital-based cross-sectional study was carried out with 40 purposively selected women aged 18 and older who were diagnosed with secondary postpartum hemorrhage and admitted more than 24 hours after childbirth or during the puerperal period. A pre-tested semi-structured questionnaire was used to interview these women in the Department of Obstetrics and Gynaecology at Sylhet MAG Osmani Medical College Hospital in Bangladesh. Results: Three-quarters of the participants (75.0%) were in the 18–30 age range, with an average age of 27.6±4.7 years.Among the patients, 20.0% reported issues during a previous pregnancy, and 65.0% experienced complications in their last delivery.Among the patients, 32.5% delivered in a hospital, while 67.5% gave birth at home. Of the total, 25.0% underwent a cesarean section, while 75.0% had a vaginal delivery. Additionally, 70.0% of the patients with secondary postpartum hemorrhage experienced varying degrees of anemia, ranging from mild to severe. Retained placental fragments were the primary cause of secondary PPH, accounting for 52.5% of cases, while endometritis and subinvolution each contributed to 15% of the cases. Conclusion: Enhancing awareness of the predictive factors for secondary PPH could significantly contribute to the recognition and management of postpartum morbidity and mortality Chatt Maa Shi Hosp Med Coll J; Vol.24 (2); July 2025; Page 3-7